Analisis Efisiensi Manajemen Persediaan Bahan Bakar Minyak (BBM) Menggunakan Metode Economic Order Quantity (EOQ) di PT XYZ - Irawan, Heri Tri; Balqis, Syarifah Naila; Pamungkas, Iing; Pandria, T.M. Azis; Hadi, Khairul; Muzakir, Muzakir (Universitas Teuku Umar, 2025)
This study analyzes the efficiency of diesel fuel inventory management at PT. XYZ, located in Desa Peunaga Cut Ujong, Kecamatan Meureubo, Kabupaten Aceh Barat, Aceh. The main problem faced by the company is inefficient fuel inventory management, leading to a mismatch between stock and usage, potential equipment downtime, and high inventory costs. The research objective is to evaluate PT. XYZ's current fuel inventory policy and compare it with the application of the Economic Order Quantity (EOQ) method to identify potential improvements in efficiency and cost savings. The research method used is a quantitative approach with a comparative descriptive design. Secondary data, including records of fuel purchases, usage, and ordering and holding costs for 2024, were collected from PT. XYZ's Supply Chain Management (SCM) division, supplemented by primary data from interviews. Data analysis involved calculating EOQ, determining optimal ordering frequency, safety stock, reorder point, and comparing the Total Inventory Cost (TIC) between the company's existing policy and the EOQ method. The results indicate that PT. XYZ's current fuel inventory management policy incurs significantly higher Total Inventory Costs (TIC) compared to those achievable using the EOQ method. Implementing EOQ substantially optimizes order quantity, frequency, safety stock, and reorder point, which in turn can lead to considerable cost reductions. This suggests that adopting the EOQ recommendations can improve operational efficiency and provide financial benefits for PT. XYZ.